PKM. PENULISAN PENELITIAN TINDAKAN KELAS DAN PUBLIKASI ILMIAH GURU DI SMAK NEGERI 3 SUKAWATI - I Komang Sukendra; I Wayan Sumandya; Putu Dessy Fridayanthi; I Made Surat (LPPM Universitas PGRI Mahadewa Indonesia, 2021)
Classroom Action Research (CAR) is a study that raises actual problems faced by teachers in the field. By implementing CAR, teachers have a dual role as practitioners and researchers. The purpose of this service is to provide socialization and deepening in the writing of PTK and scientific articles to be published in ISSN and accredited journals. HTA training is carried out at SMK Negeri 3 Sukawati starting with a systematic study of the problem. CAR is very useful for teachers to improve the quality of the process and learning outcomes in the classroom. The methods used are socialization and mentoring. Components in the action research cycle (1) plan, (2) action, (3) Observation (4) Reflective. In accordance with book 4 and book 5 teacher professional guidance and development, journal requirements that can contain scientific articles include: published by universities, professional organizations, ministries, non-ministerial government agencies, research and development institutions, educational institutions, involving qualified bestari partners. with journals from various universities, has e-ISSN, maintains consistency in writing style and appearance format, has a DOI or digital object identifier. There is one thing that must be considered so that the HTA and Journal articles can pass the Credit Score assessment by the Assessment Team, namely the principles of APIK (Original, Necessary, Scientific, and Consistent).